Zawartość kadmu w glebach strefy ochronnej Huty Miedzi Głogów = Changes of the cadmium concentration in soils from the protective zone of the Głogów copper smelter - Kostecki, Jakub (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The area of the protective zone of the Głogów copper smelter was exposed to pollution for three decades. This article presents the results of the changes of total cadmium concentration in soils of this area.
Keywords: strefa ochronna; gleba; monitoring; kadm; protective zone; soils; cadmium